Class II functional orthopaedic treatment: a systematic review of systematic reviews. (31st March 2015) - D'Antò, V.; Bucci, R.; Franchi, L.; Rongo, R.; Michelotti, A.; Martina, R.
Summary This Systematic Review (SR) aims to assess the quality of SRs and Meta‐Analyses (MAs) on functional orthopaedic treatment of Class II malocclusion and to summarise and rate the reported effects. Electronic and manual searches were conducted until June 2014. SRs and MAs focusing on the effects of functional orthopaedic treatment of Class II malocclusion in growing patients were included. The methodological quality of the included papers was assessed using the AMSTAR (Assessment of Multiple Systematic Reviews). The design of the primary studies included in each SR was assessed with Level of Research Design scoring. The evidence of the main outcomes was summarised and rated according to a scale of statements. 14 SRs fulfilled the inclusion criteria. The appliances evaluated were as follows: Activator (2 studies), Twin Block (4 studies), headgear (3 studies), Herbst (2 studies), Jasper Jumper (1 study), Bionator (1 study) and Fränkel‐2 (1 study). Four studies reviewed several functional appliances, as a group. The mean AMSTAR score was 6 (ranged 2–10). Six SRs included only controlled clinical trials (CCTs), three SRs included only randomised controlled trials (RCTs), four SRs included both CCTs and RCTs and one SR included also expert opinions. There was some evidence of reduction of the overjet, with different appliances except from headgear; there was some evidence of small maxillary growth restrain with Twin Block and headgear; there was some evidence of elongation of mandibular length, but the clinical relevance of this results is still questionable; there was insufficient evidence to determine an effect on soft tissues.